Edukasi berbasis leaflet dalam upaya pencegahan infeksi menular seksual pada mahasiswa kebidanan semester 2 STIKARA Sintang - Hannisa, Silvia Finida; Gunarmi, Gunarmi; Navalia, Zesika Intan (JOURNAL of Public Health Concerns, 2026)
Background: Sexually Transmitted Infections (STIs) in Indonesia are projected to increase by 2024, particularly among adolescents and young adults. More than 311,000 deaths from cervical cancer occur annually, and STIs directly impact sexual and reproductive health through stigmatization, infertility, cancer, and pregnancy complications, as well as increasing the risk of HIV. This situation indicates that STIs remain a serious health problem in Indonesia and require prevention efforts through effective health education, particularly among young people. Purpose: To increase students' knowledge, understanding, and awareness of STIs and their prevention using leaflets. Method: This community service activity was conducted in April 2026 at STIKARA Sintang and involved 60 second-semester Midwifery students from STIKARA Sintang as respondents. The material was delivered through lectures and interactive discussions using leaflets delivered in person. Evaluation used questionnaires administered before and after the educational activity (pre-test) and after the educational activity (post-test). The questionnaire results were analyzed descriptively to determine the increase in respondents' knowledge and understanding after the education. Results: None of the respondents' knowledge levels before the educational activity (pre-test) were in the good category, with 23 (38.3%) in the sufficient category, and 37 (61.7%) in the poor category. Meanwhile, the level of knowledge of respondents after the educational activity (post-test) was 28 (46.78%) in the good category, 25 (41.7%) in the sufficient category, and 7 (11.6%) in the poor category. Conclusion: The intervention activity, which involved education using leaflets, was highly effective in increasing the knowledge and understanding of second-semester midwifery students regarding sexually transmitted infections (STIs). This increased knowledge and understanding positively contributed to the students' role as future healthcare workers in providing STI education and prevention in the community. Suggestion: Educational institutions are encouraged to conduct further research using quasi-experimental and controlled designs to assess the effectiveness of the education. It is also recommended that healthcare institutions collaborate with students in providing education as an effective and applicable strategy to increase knowledge about STIs in the community. Keywords: Adolescents; Health education; Promotion and prevention; Sexually transmitted infections; Student role Pendahuluan: Infeksi Menular Seksual (IMS) di Indonesia pada tahun 2024 meningkat, terutama pada kelompok usia remaja dan dewasa muda. Lebih dari 311.000 kematian akibat kanker serviks setiap tahun dan Penyakit Menular Seksual (PMS) berdampak langsung pada kesehatan seksual dan reproduksi melalui stigmatisasi, infertilitas, kanker, dan komplikasi kehamilan, serta dapat meningkatkan risiko HIV. Kondisi ini menunjukkan bahwa IMS masih menjadi masalah kesehatan yang serius di Indonesia dan memerlukan upaya pencegahan melalui edukasi kesehatan yang efektif, khususnya pada kelompok usia muda. Tujuan: Untuk meningkatkan pengetahuan, pemahaman dan kesadaran mahasiswa tentang Infeksi Menular Seksual dan pencegahannya dengan menggunakan media leaflet Metode: Kegiatan pengabdian masyarakat ini dilaksanakan pada bulan April 2026 di STIKARA Sintang dan melibatkan 60 mahasiswa Kebidanan Semester 2 STIKARA Sintang menjadi responden. Materi disampaikan melalui ceramah dan diskusi interaktif menggunakan media leaflet yang disampaikan secara langsung. Evaluasi penilaian menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Hasil kuesioner di analisa deskriptif untuk melihat peningkatan pengetahuan dan pemahaman responden setelah diberikan edukasi. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum kegiatan edukasi (pre-test) tidak ada yang berada dalam kategori baik, sebanyak 23 (38.3%) dalam kategori cukup dan sebanyak 37 (61.7%) dalam kategori kurang. Sedangkan tingkat pengetahuan responden setelah kegiatan edukasi (post-test) menjadi sebanyak 28 (46.78%) kategori baik, sebanyak 25 (41.7%) dalam kategori cukup dan sebanyak 7 (11.6%) dalam kategori kurang. Simpulan: Kegiatan intervensi berupa edukasi dengan menggunakan media leaflet sangat efektif dalam meningkatkan pengetahuan dan pemahaman mahasiswa Kebidanan Semester 2 mengenai Infeksi Menular Seksual (IMS). Peningkatan pengetahuan dan pemahaman mahasiswa memberikan kontribusi positif sebagai upaya promotif dan preventif terhadap peran mahasiswa sebagai calon tenaga kesehatan dalam memberikan edukasi dan pencegahan IMS di masyarakat. Saran: Diharapkan kepada institusi pendidikan untuk dilakukan penelitian lebih lanjut dengan menggunakan desain quasi-eksperimental dan kontrol untuk menilai pencapaian efek edukasi. Diharapkan juga kepada lembaga kesehatan dapat berkolaborasi dengan mahasiswa dalam kegiatan memberikan edukasi sebagai strategi yang efektif dan aplikatif dalam meningkatkan pengetahuan tentang IMS di masyarakat.